Post-necrotic cirrhosis with chronic cholestasis. Issue 3 (September 1963) - Datta, D. V.; Sherlock, Sheila; Scheuer, Peter J.
Abstract : Features of biliary obstruction were seen in 57 of 300 cases of post-necrotic cirrhosis but gave rise to real diagnostic difficulty in only 11 cases. The paper deals with the recognition and possible pathogenesis of this syndrome.